Tung oil-based production of high 3-hydroxyhexanoate-containing terpolymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) using engineered ralstonia eutropha - Lee, Hye Soo; Lee, Sun Mi; Park, Sol Lee; Choi, Tae Rim; Song, Hun Suk; Kim, Hyun Joong; Bhatia, Shashi Kant; Gurav, Ranjit; Kim, Yun Gon; Kim, June Hyung; Choi, Kwon Young; Yang, Yung Hun (Polymers, 2021)
Polyhydroxyalkanoates (PHAs) are attractive new bioplastics for the replacement of plastics derived from fossil fuels. With their biodegradable properties, they have also recently been applied to the medical field. As poly(3-hydroxybutyrate) produced by wild-type Ralstonia eutropha has limitations with regard to its physical properties, it is advantageous to synthesize co-or terpolymers with medium-chain-length monomers. In this study, tung oil, which has antioxidant activity due to its 80% α-eleostearic acid content, was used as a carbon source and terpolymer P(53 mol% 3-hydroxybytyrate-co-2 mol% 3-hydroxyvalerate-co-45 mol% 3-hydroxyhexanoate) with a high proportion of 3-hydroxyhexanoate was produced in R. eutropha Re2133/pCB81. To avail the benefits of α-eleostearic acid in the tung oil-based medium, we performed partial harvesting of PHA by using a mild water wash to recover PHA and residual tung oil on the PHA film. This resulted in a film coated with residual tung oil, showing antioxidant activity. Here, we report the first application of tung oil as a substrate for PHA production, introducing a high proportion of hydroxyhexanoate monomer into the terpolymer. Additionally, the residual tung oil was used as an antioxidant coating, resulting in the production of bioactive PHA, expanding the applicability to the medical field.
Keywords: 3-Hydroxyhexanoate; Anti-oxidant activities; Eleostearic acid; Medical fields; Partial harvesting; Poly-3-hydroxybutyrate; Polyhydroxyalkanoates; Ralstonia eutropha; Antioxidant; PHA; Polyhydroxyalkanoates; Ralstonia eutropha; Tung oil; α-eleostearic acid